1987
DOI: 10.3386/w2404
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Obsolescence, and the Productivity Slowdown

Abstract: for their comments and help. The research reported here is part of the NBERs research program in Productivity. Any opinions expressed are those of the authors and not those of the National Bureau of Economic Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 6 publications
2
19
0
1
Order By: Relevance
“…do not need to bother with the suggested adjustments for the longevity of the capital stocks in the economy. This corroborates the evidence presented by Hulten and Wykoff (1989). However, as these variables and parameters varied significantly from one year to the other, in all probability the useful lives varied significantly as well.…”
Section: Summary Of Findings and Conclusionsupporting
confidence: 90%
See 1 more Smart Citation
“…do not need to bother with the suggested adjustments for the longevity of the capital stocks in the economy. This corroborates the evidence presented by Hulten and Wykoff (1989). However, as these variables and parameters varied significantly from one year to the other, in all probability the useful lives varied significantly as well.…”
Section: Summary Of Findings and Conclusionsupporting
confidence: 90%
“…1 On the side of econometric applications here is how Hulten et al (1989) expressed the usefulness of the proportionality hypothesis: " We have found that a major event like energy crises, … did not in fact result in a systematic change in age-price profiles. This lends confidence to procedures that assume stationarity in order to achieve a major degree of simplification (and because of nonstationarity is so difficult to deal with empirically).…”
Section: Endnotesmentioning
confidence: 99%
“…88 Of course, geometric depreciation has the disadvantage that it will never exhaust the full value of the asset. 89 Finally, a good alternative to the geometric depreciation model is the linear efficiency decline model.…”
Section: Resultsmentioning
confidence: 99%
“…12 Im Rahmen dieser Arbeit wird wie erwähnt stets unterstellt, dass Ölpreisschocks mit den Veränderungen der Preise anderer Energieträger hoch korreliert sind. 13 Kim, Loungani (1992: 182-186 (Rotemberg, Woodford 1996: 555-572 (Rotemberg, Woodford 1996: 557-558 (Hulten et al 1989;Bohi 1991: 157-158).…”
Section: Grundsätzliche Theoretische üBerlegungenunclassified